Pengaruh Beban Kerja dan Dukungan Organisasi Terhadap Stres Kerja: Peran Mediasi Resiliensi pada Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) - Suhaili Suhaili; Sumardin Sumardin; Mulyadi Mulyadi (Jayapangus Press, 2026)
Work stress is an issue that needs attention among Government Employees with Work Agreements (Pegawai Pemerintah dengan Perjanjian Kerja/PPPK), particularly when high job demands are not accompanied by adequate organizational support. Such conditions may affect employees’ psychological well-being and work performance. This study aims to analyze the effects of workload and organizational support on job stress and to examine the role of resilience as a mediating variable among PPPK employees at the Marine and Fisheries Agency of the Riau Islands Province. This study employed a quantitative approach involving 136 PPPK respondents. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4. The results showed that workload had a positive and significant effect on resilience (β = 0.546; p < 0.001) and job stress (β = 0.602; p < 0.001). Organizational support did not have a significant effect on resilience (β = 0.179; p = 0.099), but had a negative and significant effect on job stress (β = -0.225; p = 0.013). Resilience did not have a significant effect on job stress (β = -0.091; p = 0.430). Resilience was also not proven to mediate the effects of workload or organizational support on job stress. In conclusion, workload and organizational support have direct effects on job stress among PPPK employees, while resilience has not been proven to function as a mediator in these relationships.